Biofuel crop sustainability - Singh, Bharat P. (Ames, Iowa : Wiley-Blackwell, 2013)
Biofuel Crop Sustainability brings together the basic principles of agricultural sustainability and special stipulations for biofuels, from the economic and ecological opportunities and challenges of sustainable biofuel crop production to the unique characteristics of particular crops which make them ideal for biofuel applications. This book will be a valuable resource for researchers and professionals involved in biofuels development and production as well as agriculture industry personnel. Chapters focus the broad principles of resource management for ecological, environmental and s.
Biofuel crop sustainability paradigm / Bharat P. Singh -- Sustainable production of grain crops for biofuels / Abdullah A. Jaradat -- Sugarcane as an energy crop: its role in biomass economy / Rianto van Antwerpe [and others] -- Sustainable cellulosic grass crops production / John H. Fike, David J. Parrish and Wonae B. Fike -- Sustainable oil crops production / C. Eynck [and others] -- Short-rotation woody crop biomass production for bioenergy / Chris L. Kiser and Thomas R. Fox -- Biomass feedstock production impact on water resource availability / K.C. Stone [and others] -- Biofuel crops and soil quality and erosion / Dmitri Chatskikh [and others] -- Nutrient management in biofuel crop production / Rocky Lemus -- Food, farming, and land use for biofuels / József Popp -- Biofuel crops and ecosystem services and biodiversity / Andrew Fieldsend and Hari P. Singh -- Biofuel crops and greenhouse gases / A. Hastings [and others] -- Economics of biomass feedstocks and biofuels / Thein A. Maung [and others] -- Geospatial modeling applications for biofuel sustainability assessment / Sudhanshu S. Panda.
Includes bibliographical references and index.
Print version record.
Keywords: Energy crops; Sustainable agriculture; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Energy crops; Sustainable agriculture; Electronic books